2015
DOI: 10.11622/smedj.2015010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lesions and measurement of salivary pH in the different trimesters of pregnancy

Abstract: INTRODUCTIONMany epidemiological studies on the prevalence of oral lesions and dental health status of pregnant women have been conducted worldwide.(1-6) However, data on the prevalence of oral lesions in the different trimesters of pregnancy is scarce. Investigations that have been done in the different trimesters are mainly restricted to dental health status and not many factors have been studied. Therefore, this study was undertaken to assess the prevalence of oral lesions during the different trimesters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 20 publications
0
44
1
10
Order By: Relevance
“…During pregnancy, dietary changes are common, such as regular consumption of snacks, sugary drinks, and citrus foods, to satisfy desires or prevent nausea. Such habits may lead to a drop in salivary pH, thus favoring an increase in the number of acidophilic microorganisms . Jain and Kaur observed an increase of Streptococcus mutans and Lactobacillus levels, especially in late pregnancy, comparing the saliva of pregnant with non‐pregnant women …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, dietary changes are common, such as regular consumption of snacks, sugary drinks, and citrus foods, to satisfy desires or prevent nausea. Such habits may lead to a drop in salivary pH, thus favoring an increase in the number of acidophilic microorganisms . Jain and Kaur observed an increase of Streptococcus mutans and Lactobacillus levels, especially in late pregnancy, comparing the saliva of pregnant with non‐pregnant women …”
Section: Resultsmentioning
confidence: 99%
“…It can be deduced that most of these effects on the oral tissues during pregnancy could be avoided by practicing proper oral hygiene and clinical dental follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…13 A low salivary pH can reduce absorption, as less of the drug would be unionized, and this could contribute to a smaller AUC during pregnancy. In our population, salivary pH did not differ between groups, and therefore, was not correlated with changes in AUC 0→12 , Cmax, Tmax nor dissolution time.…”
Section: Commentmentioning
confidence: 99%
“…6,12,13,15,[19][20][21][22][23][24] Among all the analysis performed, and taking together previous studies and the present study, we can confidently assume that pregnancy reduces non-stimulated saliva pH. 6,12,13,19,21 The decrease of saliva pH during pregnancy may be partially justified by the higher number of daily meals. 6,26 The acidic saliva throughout pregnancy represents a risk factor for dental caries development.…”
Section: ■ Discussionmentioning
confidence: 60%
“…14,15,21,23,34,35 Regarding salivary flow rate, most studies, including ours, reported no changes between pregnant and nonpregnant women; 6,13,19,20 however, Naveen et al 12 showed higher rates for either stimulated or non-stimulated saliva. In addition, reports regarding salivary flow rate throughout pregnancy are controversial, 34,35 suggesting that many factors may regulate this flow during pregnancy.…”
Section: 1931-33mentioning
confidence: 60%